2022
DOI: 10.1364/ol.471850
|View full text |Cite
|
Sign up to set email alerts
|

All-optical, tunable, V- and W-band microwave generation using semiconductor lasers at period-one nonlinear dynamics with asymmetric mutual injection stabilization

Abstract: This study investigates an optically injected semiconductor laser operating at period-one nonlinear dynamics for all-optical microwave generation. A novel, to the best of our knowledge, all-optical stabilization scheme is proposed to greatly enhance the spectral purity of such generated microwaves, which sends a small fraction of the injected laser output back to the injecting laser, not the injected laser itself. Mutual injection with highly different injection power between the two lasers, i.e., highly asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Photonic generation of high-quality single-frequency microwaves [1][2][3][4] and multi-frequency microwave combs [5,6] using nonlinear semiconductor laser dynamics has been theoretically studied and experimentally investigated. When semiconductor lasers are optically injected by single-frequency optical continuous waves at the hopf bifurcation point [1], the semiconductor lasers are destabilized at a fundamental oscillation frequency f0, known as Period-one (P1) frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photonic generation of high-quality single-frequency microwaves [1][2][3][4] and multi-frequency microwave combs [5,6] using nonlinear semiconductor laser dynamics has been theoretically studied and experimentally investigated. When semiconductor lasers are optically injected by single-frequency optical continuous waves at the hopf bifurcation point [1], the semiconductor lasers are destabilized at a fundamental oscillation frequency f0, known as Period-one (P1) frequency.…”
Section: Introductionmentioning
confidence: 99%
“…When semiconductor lasers are optically injected by single-frequency optical continuous waves at the hopf bifurcation point [1], the semiconductor lasers are destabilized at a fundamental oscillation frequency f0, known as Period-one (P1) frequency. While the microwave quality of the P1 dynamics typically suffers from the semiconductor laser noise and the associated instabilities, several studies have demonstrated that double-locking [1], phase-locking [2], cascaded injectionlocking [3] and mutual injection-locking [4] are feasible approaches for high-quality microwaves generation using the stabilized P1 dynamics. Optical frequency combs (OFCs) are coherent light sources having discrete series of evenly spaced (MHz ~ GHz) spectral components.…”
Section: Introductionmentioning
confidence: 99%